Beta-Blocker Use during Pregnancy Correlates with Less Aortic Root Dilatation in Patients with Marfan's Syndrome - Roberts, Emma A.; Pistner, Andrew; Osobamiro, Oyinkansola; Banning, Stephanie; Shalhub, Sherene; Albright, Catherine; Horovitz, Ofir; Buber, Jonathan (AORTA, 2023)
Background Pregnant patients with Marfan's syndrome (MFS) are at an increased risk for adverse aortic outcomes. While beta-blockers are used to slow aortic root dilatation in nonpregnant MFS patients, the benefit of such therapy in pregnant MFS patients remains controversial. The purpose of this study was to investigate the effect of beta-blockers on aortic root dilatation during pregnancy in MFS patients.Methods This was a longitudinal single-center retrospective cohort study of females with MFS who completed a pregnancy between 2004 and 2020. Clinical, fetal, and echocardiographic data were compared in patients on- versus off-beta-blockers during pregnancy.Results A total of 20 pregnancies completed by 19 patients were evaluated. Beta-blocker therapy was initiated or continued in 13 (65%) of the 20 pregnancies. Pregnancies on-beta-blocker therapy experienced less aortic growth compared with those off-beta-blockers (0.10 [interquartile range, IQR: 0.10–0.20] vs. 0.30 cm [IQR: 0.25–0.35]; p = 0.03). Using univariate linear regression, maximum systolic blood pressures (SBP), increase in SBP, and absence of beta-blocker use in pregnancy were found to be significantly associated with greater increase in aortic diameter during pregnancy. There were no differences in rates of fetal growth restriction between pregnancies on- versus off-beta-blockers.Conclusion This is the first study that we are aware of to evaluate changes in aortic dimensions in MFS pregnancies stratified by beta-blocker use. Beta-blocker therapy was found to be associated with less aortic root growth during pregnancy in MFS patients.
Keywords: Marfan's syndrome; pregnancy; beta-blockers; aorta; aortic dilation